Electrochemical oxidative dearomatization of 2-arylthiophenes. Issue 11 (22nd April 2022) - Shi, Zhaojiang; Lu, Hao-Kuan; Li, Nan; Yuan, Yaofeng; Li, Zhen; Ye, Ke-Yin
Abstract : A green and sustainable electrochemical oxidative dearomatization of 2-arylthiophenes has been developed toward the preparation of both C2/C3 and C2/C5 difunctionalized thiophenones. Abstract : Herein we report a green and sustainable electrochemical oxidative dearomatization of 2-arylthiophenes. The variation of substitution patterns affords easy access to both C2/C3 and C2/C5 difunctionalized dearomative products. The synthetic utility of the resulting dihydrothiophenes is further demonstrated by the concise synthesis of a pyridazinone analog with interesting vasodilator activity.